Laser-induced two-dimensional bubble and jet - Wong, Chu Ping (2015)
This project investigates the physical characteristics of induced bubbles and microjet formation in distilled water within a two-dimensional (2D) volume by having four test cell heights, two cell types, using a range laser energy input. Bubble size, collapse rate and jet rate produced are measured where possible and are collated into dimensionless graphs to show relations. These measurements are collected from images recorded with high-speed cinematography using Matlab. The intent of using 2D cell spaces is to enhance the effects of friction and viscosity in contrast to thermodynamic effects that affect the collapse and jet formation mechanisms. Results shed more light on how the investigated parameters (energy absorbed, cell height) can affect bubble radius and initial jet velocity.